THE APPLICATION OF THE HORAY COURSE REVIEW MODEL WITH AFFECTIVE STRATEGIES TO IMPROVE LEARNING OUTCOMES ISLAMIC RELIGIOUS EDUCATION - Nurpadilah, Alimah; Ma'shum, Sya'roni; Permana, Higil (Universitas Islam Madura, 2025)
This research aims to improve student learning outcomes in PAI subjects through the application of the CRH model with affective strategies in students in grade VIII-A SMP Negeri 2 West Karawang. The research method uses a quantitative approach with a class action research (PTK) design which is carried out in two cycles, each consisting of stages of planning, implementation, observation, and reflection. The subjects of the study were 40 students of class VIII-A. Data collection instruments are in the form of learning outcome tests and observation sheets of student activities during learning. Data analysis was carried out descriptively by comparing the results between cycles. The results of the study show that the application of the CRH model with affective strategies has a positive impact on student learning outcomes. In the first cycle, the level of learning completeness only reached 66.6% with the category of lacking. However, after improvements and the implementation of actions in cycle II, the completeness rate increased significantly to 82.4% with the good category. This improvement shows that the CRH model is able to create a more interesting learning atmosphere, foster motivation, and increase active student engagement. Thus, it can be concluded that the use of the Horay Course Review model with affective strategies is effective in improving PAI learning outcomes. This model is worthy of being implemented more widely in learning, especially in materials that require strengthening concept understanding as well as developing positive attitudes of students.